An improved CryoSat-2 sea ice freeboard retrieval algorithm through the use of waveform fitting - Kurtz, N. T.; Galin, N.; Studinger, M. (The Cryosphere, 2014)
We develop a physical model capable of simulating the mean echo power of CryoSat-2 SAR- and SARIn-mode waveforms over sea-ice-covered regions. The model simulations are used to show the importance of variations in the radar backscatter coefficient with incidence angle and surface roughness for the retrieval of surface elevation of both sea ice floes and leads. The physical model is used to fit CryoSat-2 waveforms to enable retrieval of surface elevation through the use of lookup tables and a bounded trust region Newton least-squares fitting approach. The use of a model to fit returns from sea ice regions offers advantages over currently used threshold retracking methods, which are here shown to be sensitive to the combined effect of bandwidth-limited range resolution and surface roughness variations. Laxon et al. (2013) have compared ice thickness results from CryoSat-2 and IceBridge, and found good agreement; however consistent assumptions about the snow depth and density of sea ice were not used in the comparisons. To address this issue, we directly compare ice freeboard and thickness retrievals from the waveform-fitting and threshold tracker methods of CryoSat-2 to Operation IceBridge data using a consistent set of parameterizations. The purpose of the comparison is to highlight the physical basis between differences in the retracking methods. For three IceBridge campaign periods from March 2011 to March 2013, mean differences (CryoSat-2 – IceBridge) of 0.144 and 1.351 m are found between the freeboard and thickness retrievals, respectively, using a 50% sea ice floe threshold retracker, while mean differences of 0.019 and 0.182 m are found when using the waveform-fitting method. This suggests the waveform-fitting technique is capable of better reconciling the sea ice thickness data record from laser and radar altimetry data sets through the usage of consistent physical assumptions.